Design of information architecture for flexible manufacturing systems - Jambak, Muhammad Ikhwan (2000)
A complete set of manufacturing information is needed by various machines and entities in order to operate a flexible manufacturing system (FMS) efficiently. The use of an information architecture in order to develop a manufacturing information system is well known in Computer-Integrated Manufacturing (CIM), but the application of it is still limited. One of the main reasons is that existing information architectures are too general. A major effort is still required in developing and customising the information systems for an FMS. This research studies the existing CIM life cycle architectures in order to propose a framework to develop a generalised flexible manufacturing information system. The manufacturing functions and detail information needed by a generalised FMS are modelled at the conceptual design stage of this proposed framework by using IDEF modelling language. The results of the modelling work includes the proposed functional and information reference models which are components of the information architecture. The proposed information model is then successfully implemented both on a PC-based and Client-Server database Platforms. A case study involving a small real life CIM system that consists of the common FMS elements was then made. In this case study the information requirements of the system were first modelled and defined. The information architecture was then adopted to suit the particular CIM system characteristics. Based on this, a suitable database information system for the FMS system was developed. The framework adopted was seen to have the following advantages. Firstly, the reference model developed in this research was generally applicable to develop a manufacturing information system. Secondly, it proved easier to customise using the reference model as a template compared to developing the information system from scratch. The proposed information architecture will assist manufacturing database developers to develop their own manufacturing database system based on their own specific requirements.